Same same but different. Are there differences in technique between training and competition in youth cross-county skiing? - Fudel, R.; Eberhardt, A. (Science and Skiing VIII. Book of the 8th International Congress on Science and Skiing, 2020)
Cross-country skiing is one of few endurance sports which includes a variety of disciplines, techniques and sub techniques in different terrains. In addition gliding on snow is a very specific ability with limited training times and opportunities. To perform cross-country skiing on elite level, an athlete must be able to master these abilities. Therefore technique is an important performance prerequisite and should be an essential part of iong-term athlete development in this sport (Stöggl & Stöggl, 2013). Youth coaches of the German Skiing Federation currently assess their athletes` technical level as not sufficient for later top performances in elite sports. They claim that the deficiencies crept into technique during childhood and adolescence are still present and difficult to correct in adult age. The current competition system as well as the Talent ID-programs in Germany consists mainly on regular races where matured athletes have advantages even if their technique s inadequate. To improve technique training and increase its value in talent identification, the goal of the study is to develop an assessment scheme for analysing technical characteristics. However, there are controversial opinions whether the assessment should be executed in training or competition. Of course, it is easier to focus on technique in training and especially in youth age the quality might be (but not must be necessarily) higher (Schücker & Parrington, 2018). In the end, the athletes must be able to perform with their best technique in competition. Improving technique usually happens in training but the transfer to competition is rarely examined. Thus, the aim of this study was to evaluate biomechanical differences in technique between training and competition in youth cross-country skiing.